1996
DOI: 10.1177/44.8.8756757
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies reactivities of anti-human macrophage monoclonal antibodies to various animal species.

Abstract: We examined interspecies reactivities of eight anti-human monocgte/maaophage monoclonal antibodies (MAbs), AM-3K, PM-2K, X4, X14, Bet-MAC3, GHIl61, EBMl11, and KP1, with various animal h e s including rats, guinea pigs, rabbits, cats, dogs, goats, pigs, M e s , horses, andmonkeys. All MAbs recognized monkey macrophages. Pig macrophages were detected by most MAbs except for EBMlll and KP1. Ofthe eight antibodies, AM3K showed the widest intespecies reactivity. It reacted with macrophages of all animal species ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 3 publications
(6 reference statements)
2
32
0
Order By: Relevance
“…Slides were counterstained with eosin. The following primary antibodies were used for immunohistochemistry: goat anti-human polyclonal antibody to MCSF (Santa Cruz Biotechnology, Santa Cruz, CA), polyclonal antibody to c-Fms (Santa Cruz), mouse monoclonal antibody to proliferating cell nuclear antigen (PCNA; clone PC10, Dako; Carpinteria, CA) (13,14), monoclonal macrophage 387 (Mac387) antibody (Dako) (15), mouse anti-CD31 antibody (Dako) (13) anti-human antibody to collagen type III clone IV-4h12 (IGN Biomedicals; Aurora, OH) and monoclonal anti-macrophage antibody PM-2K (Biogenesis; Kingston, NH) (44). The Mac387 antibody detects an epitope on the calcium-binding protein MRP14 (17), which is highly expressed in monocytes and rapidly downregulated in mature macrophages (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slides were counterstained with eosin. The following primary antibodies were used for immunohistochemistry: goat anti-human polyclonal antibody to MCSF (Santa Cruz Biotechnology, Santa Cruz, CA), polyclonal antibody to c-Fms (Santa Cruz), mouse monoclonal antibody to proliferating cell nuclear antigen (PCNA; clone PC10, Dako; Carpinteria, CA) (13,14), monoclonal macrophage 387 (Mac387) antibody (Dako) (15), mouse anti-CD31 antibody (Dako) (13) anti-human antibody to collagen type III clone IV-4h12 (IGN Biomedicals; Aurora, OH) and monoclonal anti-macrophage antibody PM-2K (Biogenesis; Kingston, NH) (44). The Mac387 antibody detects an epitope on the calcium-binding protein MRP14 (17), which is highly expressed in monocytes and rapidly downregulated in mature macrophages (19).…”
Section: Methodsmentioning
confidence: 99%
“…It is known to cross-react with canine species (15). The monoclonal antibody PM-2K identifies mature macrophages and has been previously used in canine tissues (44). Appropriate positive and negative controls were used for each antibody.…”
Section: Methodsmentioning
confidence: 99%
“…26 To detect the BM-derived cells labeled with green fluorescence, samples were snap-frozen and cut with a cryostat. These were incubated with anti-desmin (clone DE-R-11, Dako), anti-vimentin (clone V9, Dako), anti-macrophage (PM-2K), 27 and anti-factor VIII antibody, followed by incubation with FITC-or TRITC-conjugated secondary antisera. The infarction area was evaluated by tetrazolium red staining.…”
Section: Immunohistochemistry and Analyses Of Vessel Numbersmentioning
confidence: 99%
“…For immunostaining, these segments were immediately embedded in OCT compound without fixation, frozen, and cut into 5-m-thick slices. Serial cryosections were stained with an antibody to human macrophages (PM-2K) 28 or to rat MCP-1 (clone C4) 29 or nonimmune mouse IgG (Zymed Laboratory). In a preliminary study, we confirmed that those antibodies cross-react well with porcine macrophages and MCP-1, respectively.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%